Transforming Financial Performance In Culinary SMEs: The Impact Of Organizational Culture And CSR On Financing Decisions - Dewa Ayu Inten Mahaputri; Ni Luh Anik Puspa Ningsih; Ni Wayan Sitiari (Fakultas Ekonomi Universitas Warmadewa, 2026)
Small and Medium Enterprises (SMEs) play a crucial role in supporting Indonesia’s economy, including in Bali Province, which is widely recognized as a national tourism hub. Among the dominant sectors, culinary SMEs significantly contribute to employment and economic growth. However, these enterprises continue to face challenges in maintaining financial performance due to limited innovation, digitalization, and access to financing. This study aims to examine the influence of organizational culture and Corporate Social Responsibility (CSR) on financing decisions and financial performance among culinary SMEs in Bali, with financing decisions serving as a mediating variable. A quantitative approach was employed using Partial Least Squares (PLS) as the analytical tool. The respondents consisted of 100 owners or managers of culinary SMEs in Bali, selected through a structured questionnaire survey. The findings reveal that organizational culture does not have a significant effect on either financial performance or financing decisions, suggesting that local cultural values, such as jengah, taksu, and menyamabraya, have not yet been effectively translated into financially impactful business strategies. Conversely, CSR demonstrates a positive and significant influence on both financial performance and financing decisions, indicating that social and environmental commitment enhances trust and improves access to funding for SMEs. Furthermore, financing decisions have a positive and significant impact on financial performance, serving as a mediating mechanism in the relationship between CSR and financial performance.